2015
DOI: 10.1039/c5nr04375a
|View full text |Cite
|
Sign up to set email alerts
|

Chirality control of self-assembled achiral nanofibers using amines in their solid state

Abstract: Although there are numerous examples of helical and spiral conformations in nature, including plant tendrils, snail shells, and even collagen, the occurrence of supramolecular systems that are able to reversibly undergo solid-to-solid helical transformation based on environmental chiral triggers is rare. In this work, we present a supramolecular, non-helical nanofiber which shows a distinct helical rearrangement in the presence of specific diamines and monoamines, such as cyclohexanediamines, alanine, lysine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Diaminocyclohexane (DAC) is usually used as chiral additive to control the supramolecular chirality of achiral molecular assemblies. 58,59 As shown in Figure S18, CPL signs of BTABA assemblies were controlled by adding an equivalent of DAC. Samples with Ror S-type DAC displayed a negative or a positive CPL, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diaminocyclohexane (DAC) is usually used as chiral additive to control the supramolecular chirality of achiral molecular assemblies. 58,59 As shown in Figure S18, CPL signs of BTABA assemblies were controlled by adding an equivalent of DAC. Samples with Ror S-type DAC displayed a negative or a positive CPL, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We also compared the seeds-involved VAA method and the commonly used strategy based on “sergeant–soldier rule” with chiral molecules to control the chirality after symmetry breaking. Diaminocyclohexane (DAC) is usually used as chiral additive to control the supramolecular chirality of achiral molecular assemblies. , As shown in Figure S18, CPL signs of BTABA assemblies were controlled by adding an equivalent of DAC. Samples with R - or S -type DAC displayed a negative or a positive CPL, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Jung et al. described gelator nanofibers formed by an achiral disc‐like azobenzoic acid that exhibited enantioselectivity to chiral amines . The CD spectra of the nanofibrous gels in the presence of asymmetric diamine ((1 R ,2 R )‐ and (1 S ,2 S )‐DACH) were observed to determine the chiroptical response.…”
Section: Chiral Recognition Detected By Adsorption Spectra and CD Spmentioning
confidence: 99%
“…Jung et al described gelator nanofibers formed by an achiral disc-likea zobenzoic acid that exhibited enantioselectivity to chiral amines. [56] The CD spectra of the nanofibrous gels in the presence of asymmetric diamine ((1R,2R)-and (1S,2S)-DACH) were observed to determine the chiroptical response. In the case of (1R,2R)-DACH, an egative CD signalw as obtained for the first Cotton effect at l = 432 nm, which confirmed the lefthandedh elical orientation and was consistent with SEM images.…”
Section: Chiral Recognition Detected By Adsorption Spectra and CD Spementioning
confidence: 99%
“…With the development of supramolecular chemistry, it has been found that low‐molecular‐weight compounds can self‐assemble into a variety of helical nanostructures through non‐covalent interactions. The handedness of the self‐assemblies is controlled by the chirality of the compounds and the surrounding conditions . Nanomaterials can also be shaped into helical structures.…”
Section: Introductionmentioning
confidence: 99%